Design and Trajectory Optimization of Traffic Cone Recovery Manipulator based on Groove Cam Joint - Yushan Li; Hairong Guo; Xiangyuan Hu; Lü Antao (Jixie chuandong)
Based on a dual parallel four-bar mechanism and gear joint series-type traffic cone recovery manipulator, which has the problem of low recovery efficiency and difficult to achieve optimal motion trajectory of fixed gear ratio joints. The grooved cam joint is used for improving design. Firstly, based on the motion analysis of the manipulator, the minimum main arm angle is taken as the optimization target, the constraint condition is determined according to the traffic cone motion requirement, the motion trajectory optimization model is established, and the optimal motion trajectory of the manipulator is obtained. Then, according to the optimized motion trajectory, the theoretical contour of the grooved cam is solved by analytical method, and then the actual contour of the grooved cam is obtained. Finally, the simulation is verified by Adams. The results show that the main arm angle of the traffic cone recovery robot arm is reduced by 8.1%, the working stroke of the hydraulic cylinder is shortened, the force of the hydraulic cylinder is improved, and the working efficiency of the traffic cone recovery robot arm is improved.